The Role of AI in Delaying Divorce Leading to Infidelity: Perspectives from Islamic Law and Family Psychology - Nasution, Zainul Aziz (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
Divorce delay often generates negative impacts, including infidelity. This article examines the role of Artificial Intelligence (AI) in detecting social risks resulting from delayed divorce that leads to a wife’s infidelity, viewed from the perspectives of Islamic law and family psychology. This study employs a qualitative method through literature review of Islamic law, family psychology, and AI technology. The findings indicate that AI functions as an early detection tool for signs of conflict, emotional dissatisfaction, and the risk of infidelity. From the standpoint of Islamic law, postponing divorce that results in adultery or infidelity constitutes a harm (mafsadah) that must be avoided. From a psychological perspective, prolonged delays may cause chronic stress, unmet emotional needs, and trauma in children. Therefore, AI can serve as a supportive instrument for making decisions that are more just and beneficial (maslahah).